Khung phân tích đô thị thông minh: Nghiên cứu tình huống các tỉnh/thành Đông Nam bộ - Nguyen Trong , Hoai; Nguyen Van , Dung; Tran Thi Phu , Duyen; Nguyen Van , Vien (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
The study proposes a smart city analytical framework based on the comprehensive review of theoretical and empirical studies on smart city globally, and also initially analyzes the progress to smart city of six Southeastern Vietnam provinces, including Ho Chi Minh City, Dong Nai, Binh Duong, Binh Phuoc, Tay Ninh and Ba Ria - Vung Tau. The results show that Ho Chi Minh City, with its Smart City Index (SCI) of 0.86, is the dominant city in most of the smart indicators compared to other provinces/cities in Southeastern Vietnam. Meanwhile, Binh Phuoc is ranked lowest with SCI = –0.90. Its competitiveness, infrastructure of culture, health and education are limited. Binh Duong (SCI = 0.36) has the strongest strength in local government management and foreign investment attraction. Ba Ria - Vung Tau (SCI = –0.41) has been doing well in environmental protection. While Dong Nai (SCI = 0.06) has a great advantage in economic growth, Tay Ninh is not highly regarded in the assessment of smart city development (SCI = –0.30).
Keywords: Smart city; City analytical framework; Smart City Index; Southeastern Vietnam